Information technology for management - Lucas, Henry C (Boston : Irwin/McGraw-Hill, 2000)
Counter Information Technology for Management 7/e prepares students how to take an active role in the design, use, and management of information systems and technology by providing a broad treatment of issues relating to an organization, the technology used, and how systems are developed. The main focus deals with applying technology in an organization or transforming existing systems with the use of information technology.
-- I. The Role of Managers in Information Technology 1. Using Technology to Transform the Organization 2. Interpreting and Understanding Information 3. Information Technology in Perspective II. Organizational Issues 4. Impact of IT on the Organization 5. Strategic Issues of IT 6. International Business and IT III. Information Technology 7. The Fundamentals 8. A Proliferation of Computers 9. Software is the Key 10. Database Management 11. Communications 12. Networks and Electronic Commerce 13. IT Architectures 14. System Alternatives and Acquisition IV. Systems Analysis and Design 15. Building Systems Creativity with Technology 16. Building Systems: Further Developments 17. Enhancing the Life Cycle: Packages and other Non-Traditional Techniques 18. Reengineering: Changing Businesses and Business Processes 19. Implementing Change V. Exciting Directions in Systems 20. Supporting Knowledge Workers 21. Organization Support Systems: DSS, GDSS, EIS, Groupware, Multimedia 22. Intelligent Systems VI. Issues for Senior Management 23. Management Control of IT 24. IT Issues for Management 25. Societal Implications and the Future with Technology
Includes bibliographical references (pages 713-718) and index
Keywords: Management information systems; Information technology -- Management